Amine‐Responsive Adaptable Nanospaces: Fluorescent Porous Coordination Polymer for Molecular Recognition1. Issue 44 (11th September 2014) - Haldar, Ritesh; Matsuda, Ryotaro; Kitagawa, Susumu; George, Subi J.; Maji, Tapas Kumar
Abstract Flexible and dynamic porous coordination polymers (PCPs) with well‐defined nanospaces composed of chromophoric organic linkers provide a scaffold for encapsulation of versatile guest molecules through noncovalent interactions. PCPs thus provide a potential platform for molecular recognition. Herein, we report a flexible 3D supramolecular framework [Zn(ndc)(o‐phen)]⋅DMFn (o‐phen=1, 10‐phenanthroline, ndc=2, 6‐napthalenedicarboxylate) with confined nanospaces that can accommodate different electron‐donating aromatic amine guests with selective turn‐on emission signaling. This system serves as a molecular recognition platform through an emission‐readout process. Such unprecedented tunable emission with different amines is attributed to its emissive charge‐transfer (CT) complexation with o‐phen linkers. In certain cases this CT emission is further amplified by energy transfer from the chromophoric linker unit ndc, as evidenced by single‐crystal X‐ray structural characterization.